Konten Dakwah Digital di Media Baru dalam Menghadapi Budaya Hedonisme: Perspektif Dakwah Kontemporer - Putriany; Ramsiah Tasruddin (ALAMTARA, 2025)
This study discusses digital da'wah content that is developing in new media as a response to the culture of hedonism, using a contemporary da'wah approach.. The culture of hedonism in digital media is no longer merely about pursuing personal pleasure, but has transformed into a culture of self-image, commodification of happiness, and social recognition based on digital numbers. The purpose of this study is to analyze the characteristics of the hedonistic culture that is developing in the new media ecosystem and to evaluate forms of digital da'wah content that are responsive to this phenomenon. Using a qualitative approach and library research methods, this study utilizes scientific literature sources, contemporary da'wah theory, new media theory, and hedonistic culture theory as analytical tools. The analysis technique is carried out thematically through the stages of issue categorization, theory synthesis, and critical interpretation. The results of the study indicate that the culture of hedonism in new media has three main characteristics: extreme visualization of a consumptive lifestyle, commodification of self-image as a source of happiness, and digital existence as a benchmark for social value. Responding to this, digital da'wah content has developed in three forms: (1) aesthetic narrative-visual to attract emotion and attention; (2) communicative and concise da'wah microlearning; and (3) reflective-critical content that challenges the culture of showing off and builds spiritual awareness. The implications of this research show that digital da'wah needs to play a strategic role not only as a conventional da'wah medium, but also as a counter-cultural space that presents alternative values to the dominance of hedonistic culture in the digital space.